Effects of saponins Rb1 and Re in American ginseng combined intervention on immune system of aging model - Shi, Mao; Ma, Jie; Jin, Shan; Wang, Tienan; Sui, Yuhan; Chen, Lina (Frontiers in Molecular Biosciences, 2024)
Aging is a major risk factor for the development of many pathological processes, such as reduced immunity, cancer, cardiovascular diseases or neurodegenerative diseases, while age-related chronic diseases are the most common causes of death. This paper studies the effects of American ginseng saponin Rb1 and Re alone and combined intervention on the immune system of aging mouse models, by using 30 mg/kg Rb1, 15 mg/kg Re, and Rb1 + Re (30 mg/kg Rb1 and 15 mg/kg Re (co-intervention) was used to intervene in the aging model, and immune indicators such as thymus index, spleen index, interleukin and interferon were detected to evaluate the impact of Rb1 and Re on immune function. The results show that Rb1 and Re intervention alone can increase the spleen index by 7%–12% and the thymus index by 12%–19% in the aging model. After Rb1 or Re alone intervened, the apoptotic cells in the thymus were slightly reduced, and the proportion of apoptotic cells was reduced. The combination of Rb1 + Re can promote the thymus index and spleen index to increase by 23.40% and 25.5% respectively, which is more advantageous than Rb1 or Re alone. In addition, Rb1 and Re intervention can reduce the level of interferon INF to a level comparable to that of young mice. Rb1 + Re can not only reduce the INF content, but also reduce the TNF content. The above results show that American ginseng saponin Rb1 and Re can delay the decline of the immune system in the aging model, and the combined intervention of the two is significantly better than individual intervention in the recovery of the immune system. This paper can provide theoretical basis and data support for the development of American ginseng nutritional supplements and its application in aging groups products to improve immunity.